Patient-appropriate and patient-specific quantification: Application of biomedical sciences and engineering principles for the amelioration of outcomes following reconstruction of osteochondrotomy of the sternum to access the mediastinum - Gandhi, Harjeet Singh (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2022)
It is a fact that the morphology, physiology, and load-bearing activities of two patients are never identical. The normal allometric variations in regional anatomy, primary disease processes, and co-morbid pathologies demand individual treatment planning and selection of implants for surgical repair, reconstruction, and replacement leading to patient-specific and patient-appropriate interventions. It requires quantification of hard and soft tissues of human anatomy directly or indirectly from image data and other evaluation techniques, which can be combined with reconstruction implant to form a composite structure for pre-operative evaluation. Finite element modeling and analysis are routine engineering methods to assess the safety and endurance of the physical structures, which can also be applied for the numerical evaluation of fracture reconstruction. The present study delves into the fundamentals of various imaging techniques and techniques for the acquisition of hard and soft tissue densities to extract material properties and introduces the practice of finite element methods for higher analysis and their intended surgical application.